H2 production with low carbon content via MSR in packed bed membrane reactors for high-temperature polymeric electrolyte membrane fuel cell - P. Ribeirinha (2017)
This work compares the hydrogen purity and recovery produced by a methanol steam reforming (MSR)packed bed membrane reactor (PBMR) equipped with a membrane selective to hydrogen (Pd-Ag) andwith a membrane selective to carbon dioxide (porous membrane filled with ionic liquids-ILs). A 3-dimensional non-isothermal PBMR model was developed in Fluent (AnsysTM) for simulating a PBMRequipped with these two types of membranes and simulating a conventional packed bed reactor (PBR).For the development PBMR models a MSR mechanistic kinetic model was fitted to experimental reactionrates of a commercial catalyst (BASF RP60). The results indicated that selective hydrogen removal fromthe reaction medium originates a significant increase in the methanol conversion, while the carbon dioxide removal has a smaller effect. CO2-PBMR showed to be more efficient in terms of energy consumptionthan H2-PMBR. The simulation results showed also that ILs membranes must have a minimum permeance of P1 x 106 mol s1 m2 Pa1 and CO2/H2 selectivity of P200 at 473 K to be attractive for this typeof applications. The advantages and limitations of each reactor configuration are discussed based onexperimental and simulated data.